2020
DOI: 10.1093/ije/dyaa121
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 healthcare demand and mortality in Sweden in response to non-pharmaceutical mitigation and suppression scenarios

Abstract: Background While the COVID-19 outbreak in China now appears suppressed, Europe and the USA have become the epicentres, both reporting many more deaths than China. Responding to the pandemic, Sweden has taken a different approach aiming to mitigate, not suppress, community transmission, by using physical distancing without lockdowns. Here we contrast the consequences of different responses to COVID-19 within Sweden, the resulting demand for care, intensive care, the death tolls and the associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 20 publications
1
55
0
Order By: Relevance
“…A subsets of papers use a metapopulation approach accounting also for the age-stratification and contact matrices within each subpopulation. In this group we find papers that evaluate the risks of importation of cases from China in the early phases of the pandemic [22] , model the first wave [119] , [121] , [122] , [123] , [147] and investigate reopening scenarios [106] , [120] .…”
Section: Epidemic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsets of papers use a metapopulation approach accounting also for the age-stratification and contact matrices within each subpopulation. In this group we find papers that evaluate the risks of importation of cases from China in the early phases of the pandemic [22] , model the first wave [119] , [121] , [122] , [123] , [147] and investigate reopening scenarios [106] , [120] .…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…Authors of Ref. [122] built an age-structured metapopulation model for Sweden at the municipality level. In doing so, they adopt the radiation model to estimate the mobility between subpopulations [154] before and during the pandemic.…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…The relevance of sufficiently simple contagion dynamics of this kind cannot be underestimated, particularly in recent times. There has been a continued interest in this subject as shown by [ 6 8 ], but modern and ongoing research based on SIR models can be found in [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…S4. The time-series data of total cases, hospitalised people, people in ICU and dead people for Austria come from 7 . They are reported in Fig.…”
Section: S52 Austriamentioning
confidence: 99%
“…https://de.wikipedia.org/wiki/COVID-19-Pandemie_in_\unhbox\voidb@x\bgroup\accent127O\ protect\penalty\@M\hskip\z@skip\egroupsterreich (collection of various sources), accessed on 15/12/2020 7. https://covid19-dashboard.ages.at/dashboard_Hosp.html, accessed on 15/12/2020.…”
mentioning
confidence: 99%